1998
DOI: 10.1164/ajrccm.157.4.9707094
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acid Perfusion of the Esophagus on Ventilation and Respiratory Sensation

Abstract: The relationship between gastroesophageal reflux (GER) and asthma remains controversial. Asthma symptoms worsen with GER, but are not consistently related to changes in lung function. The purpose of this study was to determine whether acid perfusion (AP) of the esophagus alters ventilation and causes respiratory symptoms. Nonasthmatic patients with normal lung function and esophageal disease (16 females and nine males, FEV1 %predicted = 99+/-9.6), underwent a Bernstein test after motility testing. Airflow, rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 27 publications
1
45
0
3
Order By: Relevance
“…Muitos estudos demonstram que a DRGE e a asma freqüentemente coexistem. Estudos com instilação ácida no esôfago, nos quais se logrou demonstrar broncoconstrição reflexa, são usados como argumento da relação entre essas duas afecções 46 . Estudos mostram que crianças e adolescentes com RGE freqüentemente apresentam sintomas respiratórios 20 .…”
Section: Asmaunclassified
“…Muitos estudos demonstram que a DRGE e a asma freqüentemente coexistem. Estudos com instilação ácida no esôfago, nos quais se logrou demonstrar broncoconstrição reflexa, são usados como argumento da relação entre essas duas afecções 46 . Estudos mostram que crianças e adolescentes com RGE freqüentemente apresentam sintomas respiratórios 20 .…”
Section: Asmaunclassified
“…In contrast to the findings of the other controlled studies of medical antireflux therapy, they were unable to show an effect of high dose omeprazole on asthma symptoms. In our acid perfusion study, we found a correlation between the severity of heartburn and the changes in minute ventilation and respiratory sensation [11]. The small number of patients with heartburn and its mild nature may explain why POSTMA and coworkers [1] were unable to show that treating reflux improved asthma symptoms and asthma medication requirements.…”
Section: Omeprazole For Asthma With Gastro-oesophageal Refluxmentioning
confidence: 63%
“…To understand the effects of GOR on respiratory sensation, nonasthmatics with normal lung function underwent AP [11]. Those patients who experienced discomfort during AP, increased their minute ventilation and respiratory sensation.…”
Section: Omeprazole For Asthma With Gastro-oesophageal Refluxmentioning
confidence: 99%
“…Animal [24] and human studies [25] confirm that distal GER may increase airways resistance and promote airway inflammation by releasing pro-inflammatory mediators [25]. FIELD et al [26] also showed that oesophageal acid increases minute ventilation, suggesting another mechanism for respiratory symptoms in GERD patients. Notwithstanding these functional changes, without aspiration parenchymal pathology does not occur.…”
Section: Mechanisms Of Respiratory Disease In Gerdmentioning
confidence: 97%